(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Ukraine is one of the richest countries in fertile soils, and the combination of a fairly favourable temperate climate makes it an agricultural region of Eastern Europe. Large-scale circulating processes often move to its territory, which leads to the formation of periods with low rainfall and high air temperature, which causes the arid phenomena such as droughts, dry winds and ect. Much attention is paid to the study of the occurrence and forecasting of the arid phenomena, as, according to the UNO estimation, the damage caused by these phenomena is 20% of the total damage caused by the natural disasters. Considering the fact that drought is a complex phenomenon that occurs due to the changes in temperature rate, lack of moisture in the atmosphere and soil, lack of precipitation, and significant evaporation from the surface, it is difficult to express it through any meteorological parameter. In addition to simple estimates, such as determining the rate of precipitation and their anomalies, complex numerical and drought indicators and indices, which can detect the presence of the arid phenomena and estimate their intensity, are used. The aim of the study is to analyze the moisture conditions on the territory of Ukraine, to determine the peculiarities of its spatial distribution under the influence of modern regional climate changes.